2019
DOI: 10.1038/s41467-019-13607-2
|View full text |Cite
|
Sign up to set email alerts
|

Audio-visual experience strengthens multisensory assemblies in adult mouse visual cortex

Abstract: We experience the world through multiple senses simultaneously. To better understand mechanisms of multisensory processing we ask whether inputs from two senses (auditory and visual) can interact and drive plasticity in neural-circuits of the primary visual cortex (V1). Using genetically-encoded voltage and calcium indicators, we find coincident audio-visual experience modifies both the supra and subthreshold response properties of neurons in L2/3 of mouse V1. Specifically, we find that after audio-visual pair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 78 publications
(94 reference statements)
3
39
1
Order By: Relevance
“…Many studies suggest that all of sensory cortex, including primary sensory areas, is multisensory 1 . For instance, mouse primary visual cortex (V1) appears to be influenced by auditory signals (Figure 1, top), which may provide global inhibition 2 , modify the neurons' orientation tuning 3,4 , boost detection of visual events 5 , or even provide tone-specific information, reinforced by prolonged exposure 6 or training 7 . These effects may be due to projections from the auditory system to the visual cortex 3,5,7 .…”
Section: Introductionmentioning
confidence: 99%
“…Many studies suggest that all of sensory cortex, including primary sensory areas, is multisensory 1 . For instance, mouse primary visual cortex (V1) appears to be influenced by auditory signals (Figure 1, top), which may provide global inhibition 2 , modify the neurons' orientation tuning 3,4 , boost detection of visual events 5 , or even provide tone-specific information, reinforced by prolonged exposure 6 or training 7 . These effects may be due to projections from the auditory system to the visual cortex 3,5,7 .…”
Section: Introductionmentioning
confidence: 99%
“…This combination of view, position and head direction may give rise to a predictive visual representation in the cortex, which will be compared to further visual input to compute error signals, as posited by predictive processing models (Fiser et al, 2016;Friston, 2005;Keller and Mrsic-Flogel, 2018;Pennartz et al, 2019;Rao and Ballard, 1999). Although this proposal needs further testing, it is generally supported by the literature documenting extensive corticocortical connections (Bizley et al, 2007;Budinger and Scheich, 2009;D'Souza et al, 2016;Felleman and Van Essen, 1991;Gămănuţ et al, 2018;Harris et al, 2019;Laramée et al, 2011;Leinweber et al, 2017), contributions to neural coding in sensory cortices by nonsensory parameters (Goltstein et al, 2013;Namboodiri et al, 2015;Pakan et al, 2018;Shuler and Bear, 2006) and auditory-visual cortical interactions (Ibrahim et al, 2016;Iurilli et al, 2012;Knöpfel et al, 2019;Meijer et al, 2020;Meijer et al, 2017;Morrill and Hasenstaub, 2018). This view does not conflict with a potential role for sensory cortices in updating spatial (e.g.…”
Section: Nature and Function Of Location-selective Firing In Sensory Corticesmentioning
confidence: 97%
“…Unisensory cortices and border regions : [Cohen, Rothschild, & Mizrahi, 2011; Deneux et al, 2019; Knöpfel et al, 2019; McClure Jr & Polack, 2019; Meijer, Montijn, Pennartz, & Lansink, 2017; Morrill & Hasenstaub, 2018; Olcese et al, 2013]…”
Section: The Neurobiology Of Multisensory Integrationmentioning
confidence: 99%
“…Over the past decade, increasing interest has focused on multisensory research in the mouse [Borges‐Merjane & Trussell, 2015; Hornix, Havekes, & Kas, 2018; Olcese et al, 2013; Radvansky & Dombeck, 2018; Reig & Silberberg, 2014]. Importantly, similar findings to the rat have emerged in the mouse, where unisensory stimuli from other modalities can impact neuronal responses in primary sensory cortices [Cohen et al, 2011; Deneux et al, 2019; Knöpfel et al, 2019; McClure Jr & Polack, 2019; Meijer et al, 2017; Morrill & Hasenstaub, 2018; Zhang, Kwon, Ben‐Johny, O'Connor, & Issa, 2020]; results that may be supported by growing evidence that primary sensory cortices may share underlying connections with one another [Massé, Ross, Bronchti, & Boire, 2017; Morrill & Hasenstaub, 2018]. As observed in the rat (Table 1), studies have also shown that the parietal cortex [Kuroki et al, 2018; Lyamzin & Benucci, 2019; Najafi et al, 2019; Song et al, 2017], orbitofrontal cortex [Sharma & Bandyopadhyay, 2019], cerebellum [Chabrol, Arenz, Wiechert, Margrie, & DiGregorio, 2015] are neuronal hubs for multisensory integration in the mouse.…”
Section: Emerging Multisensory Studies In Micementioning
confidence: 99%